2020
DOI: 10.2188/jea.je20180195
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Education and Smoking Prevalence, Independent of Occupation: A Nationally Representative Survey in Japan

Abstract: Background: Higher smoking prevalence in less educated persons and manual workers is well known. This study examines the independent relationship of education and occupation with tobacco use. Methods: We used anonymized data from a nationwide population survey (30,617 men and 33,934 women). Education was divided into junior high school, high school, or university attainment. Occupation was grouped into upper non-manual, lower non-manual, and manual. Poisson regression models stratified by age and gender were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 44 publications
10
37
0
Order By: Relevance
“…A previous regional study also showed the association between low educational background and heavy drinking in men [ 11 ] because education raises factual health-related knowledge and cognitive skills. Low educational level is also associated with other risky health behaviors in Japan [ 13 , 14 ]. Therefore, health literacy is considered to mediate educational level and health behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous regional study also showed the association between low educational background and heavy drinking in men [ 11 ] because education raises factual health-related knowledge and cognitive skills. Low educational level is also associated with other risky health behaviors in Japan [ 13 , 14 ]. Therefore, health literacy is considered to mediate educational level and health behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Regional factors may be related to both behaviors [ 10 ]. Furthermore, smoking behavior was also shown to be associated with educational level in Japan [ 13 , 14 ], and the co-use of smoking and heavy alcohol consumption more frequently exist in individuals with lower educational levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data source in this study is based on the 2010 Comprehensive Survey of Living Conditions (CSLC) conducted by the Ministry of Health, Labour and Welfare of Japan. The details of the 2010 CSLC are explained elsewhere [24]. Briefly, the CSLC covers households and their membership throughout Japan, and has been carried out annually for the purpose of collecting basic data for the promotion of national health and social welfare.…”
Section: Methodsmentioning
confidence: 99%
“…The study found that education level was signi cantly related to smoking behavior 36 . Another study conducted in Japan found a similar pattern, namely that in the group of female smokers, the level of education was signi cantly associated with current smoking behavior 37 . Also, research conducted by (Justus, SantAnna, Davanzo, & Moreira, 2020) in Brazil found a similar pattern to the above research, namely that higher education levels are associated with lower smoking probability and lower daily consumption intensity.…”
Section: Discussionmentioning
confidence: 62%